Vision, narrative, and wisdom in the Aramaic texts from Qumran: essays from the Copenhagen Symposium, 14-15 August, 2017 - Bundvad, Mette; Siegismund, Kasper; Bach, Melissa Sayyad; Holst, Søren; Høgenhaven, Jesper (Studies on the texts of the desert of Judah, 2020)
Remembering the past, cultivating a character : memory and the formation of Daniel in the Aramaic pseudo-Daniel texts (4Q243-244; 4Q245) / Andrew B. Perrin -- Transmitting patriarchal voices in Aramaic : claims of authenticity and reliability / Mika S. Pajunen -- The banquet culture in new Jerusalem, an Aramaic text from Qumran / Hugo Antonissen -- Trials and universal renewal-the priestly figure of the Levi testament 4Q541 / Torleif Elgvin -- Between Aaron and Moses in 4Qvisions of Amram / Liora Goldman -- Geography in the visions of Amram texts (4Q543-547) / Jesper Høgenhaven -- Fragments and forefathers : an experiment with the reconstruction of 4Qvisions of Amram / Søren Holst -- 4Q543 2 1-2 and the verb "to give" in Qumran Aramaic / Kasper Siegismund -- The compositional setting and implied audience of some Aramaic texts from Qumran : a working hypothesis / Daniel A. Machiela -- Aramaic traditions from the Qumran caves and the Palestinian sources for part of Luke's special material / George J. Brooke -- 4Q246 and collective interpretation / Melissa Sayyad Bach -- Fake fragments, flexible provenances : eight Aramaic "Dead Sea scrolls" from the 21st century / Arstein Justnes.